Comprehensive transcriptomic and metabolomic profiling reveals the differences between alfalfa sprouts germinated with or without light exposure - Zhang, Kangning; Li, He; Zhang, Tian; Wang, Shixing; Liu, Liang; Dong, Xuyan; Cong, Lili; Song, Hui; Wang, Aihua; Yang, Guofeng; Xie, Hongli; Wang, Zeng-Yu; et al. (Frontiers in Plant Science, 2022)
Alfalfa sprouts are among the most nutritionally rich foods, and light exposure is a critical factor in determining their biomass and quality. However, detailed metabolic and molecular differences between yellow and green alfalfa sprouts remain unclear. In this study, comprehensive metabolomic and transcriptomic analyses were integrated to evaluate the nutrient composition of alfalfa sprouts during germination with or without light exposure. Differentially expressed genes and differentially accumulated metabolites in green and yellow alfalfa sprouts were significantly enriched in secondary metabolic pathways, such as the isoflavonoid biosynthesis pathway. Green alfalfa sprouts contained a wide variety of lipids, flavonoids, phenolic acids, and terpenoids, among which the top three upregulated were calycosin, methyl gallate, and epicatechin 3-gallate, whereas yellow alfalfa sprouts contained relatively more isoquercitrin. These results provide new insights into the nutritional value and composition of alfalfa sprouts under different germination regimes.